Maternal mortality-a three-year retrospective study in a rural medical college of India - Hansda, Jayasree; Roy, Debobroto; Das, Krishnapada; Sarkar, Manojit; Das, Rumpa; Pramanik, Arpita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Maternal mortality is a tragic event as family revolves around a mother. The deadly obstetrical triad of hemorrhage, preeclampsia and infection has accounted for a third of all deaths. This study was conducted to assess maternal mortality ratio, demographic profile and causes of maternal death. Methods: This retrospective longitudinal study was conducted in the department of obstetrics and gynecology for a period of three years from 1st January 2018-31st December, 2020. Total no of death during this period was 134.Records of deaths and demographic profiles were retrieved from the medical record library of aforesaid hospital. Results: There were 134 maternal deaths amongst 56815 live births with MMR 235.85. The majority of deaths were in 20-29 year of age group and most of the deaths seen in multigravida. The 91.79% death was observed within the 24 hours and after 72 hours. Eclampsia, preeclampsia and hemorrhage were leading cause of maternal death seen in the study. Conclusions: Maternal mortality is higher than national MMR. Majority of maternal death were preventable by proper antenatal care, early detection of high-risk pregnancies and their timely referral to tertiary care centre.